Experience in implementing a patient-centered approach in a private medical organization - L. I. Moskvicheva; Yu. S. Genyush; I. A. Petrova (Исследования и практика в медицине, 2022)
Currently, taking into account the pronounced competition among modern medical organizations, attracting patients and forming a high degree of their loyalty requires significant efforts both in the field of ensuring the quality of medical services provided, and in the field of full implementation of legally enshrined patient rights, compliance with ethical and deontological norms, the formation of effective communication and integration processes between employees of a medical organization and patients and/ or their relatives, and in the context of the activities of a private medical organization, special work is also largely required to optimize the main business processes. All the activities described above are united by the concept of «patient-centered approach».Purpose of the study. To increase the degree of satisfaction of patients with the organization of medical care through the introduction of a patient-centered approach.Materials and methods. This study was undertaken using methods of analysis and synthesis, experiment and sociological measurements (questionnaires, qualitative interviews of 64 patients and 10 employees), included the study and generalization of specialized research and practical experience, work with local regulatory documents.Results. Сomprehensive work on the introduction of patient-centered principles into the activities of a medical organization had a positive impact on both the degree of patient satisfaction with the organization of medical services provided and on the assessment of modified working conditions by employees of a medical organization.Conclusion. Сonstructive optimization of the activities of a medical organization through the introduction of patient-centered principles should be carried out using an integrated approach based on international experience using project management, risk management and patient-orientation methodologies. To determine the main areas of activity and monitor the effectiveness of implemented measures, the most appropriate, relevant tools are internal audit and conducting a patient survey.